Development of an integrated scheduling model for handling equipment in automated port container terminals - Sadeghian, Syed Hamidreza (2014)
Nowadays, the role of the sea port container terminals in national and regional transportation and economy can not be omitted. Massive transportation capacity and lower carrying costs lead different countries to increase throughput of their seaport container terminals. Especially, developing countries have many plans to construct new seaport container terminals or to increase the capacity of their existing ones. To respond enormous and every increasing demand on sea transshipments within the same time frame, terminal managers require more and more efficiency in container terminal performance and operations. Automation of the processes at the quays of the container ports is one the solutions to improve the performance and output of container terminals. For such purpose, using a new generation of vehicles is unavoidable. Automated Lifting Vehicle (ALV) is one of the automatic vehicles that has been introduced during recent years and can be used in container terminals. Using ALVs, due to their ability in lifting a container from the ground by themselves, can decrease the delay of loading and unloading tasks in automatic container terminals. In other side, the integration of various types of handling equipment, is another important way to increase the efficiency of processes and productivity of a container terminal. In this research, a mixed-integer programming model is developed which considers the integration of ALVs, Quay Cranes and Yard Cranes at automated container terminals with unlimited buffer spaces. This model minimizes the delay time of the QC operations, the total traveling time of ALVs, and the total traveling time of AYCs within the storage blocks. To evaluate the performance of the developed model and solving method, numerical experiments are designed and the obtained results are reported and analyzed in this research. The results show that the application of the ALV with integrated scheduling, decreases the total travel time of vehicles, delay of quay cranes and operation time of yard cranes by 7.3% and in some cases even up to 9.3%. As the integrated scheduling of handling equipment is a “non-deterministic polynomialtime hard” (NP-hard) problem and also the computation time and ease of application are so important for real practices of the scheduling methods, So a meta-heuristic algorithm based on Genetic Algorithm is developed, in which, new operators create solutions considering the constraints of the problem and also a heuristic rule proposed which assigns the ALVs to the tasks. The results obtained from the designed test cases, show that the “Priority Based assignment” (PBA) has the best performance in this problem. In addition, results proved that the modified meta-heuristic algorithm is able to find near optimal solutions and on average, the solutions found by the GA algorithm are only 0.2% worse than the optimal solutions and in the worst case in the test cases this difference is 2.3% which is acceptable. Finally, sensitivity analysis shows that as the number of ALVs increases, the objective function decreases. Also, it is illustrated that by increasing the uncertainty in QCs' operational time, the objective function of the problem decreases slightly.